La Comunicología y la mediación social. Dos trayectorias en diálogo - Galindo Cáceres, Jesús (Mediaciones Sociales, 2007)
This text proposes a dialogue between the perspective of the social mediation developed in Manuel Martín Serrano’s book published thirty years ago, and the perspective of the Group towards a possible Communicology, GUCOM, regarding the program for a general science of communication which has existed since the year 2001. The text consists of five reports. In the first one, some ideas on change and its presence in science are presented. In the second one, some ideas on change and the social mediation are presented. In the third one, some ideas on change and the possible General Communication science are explored. In the fourth one, some elements of dialogue between the social mediation approach and the possible general Communicology are proposed. In the fifth one, the bibliographical references quoted in the first four parts can be consulted.